SQ-Met: Internet application quality validation methodology - Cortázar Goicoechea, Rebeca (2002)
SQ-Met is a project whose aim is the Internet applications Quality Assurance by means of a validation methodology for them. An innovating aspect as regards this project is that it provides a complete validation method which is suited for all the different categories of web aplications. That is to say, starting from a classification of those applications, we intend to provide a validation method which stresses the specific requirements for each category and which takes into account not only the procedure of testing to be followed (steps, tools and test cases), but also the gathering of a set of quality measures for web applications that guarantee the fulfilment of the above mentioned requirements. In this article we give a rundown of the activities that have been planned as a part of the project as well as its situation up to now.